Folic acid supplementation reduces multigenerational sperm miRNA perturbation induced by in utero environmental contaminant exposure. Issue 4 (14th December 2019) - Herst, P M; Dalvai, M; Lessard, M; Charest, P L; Navarro, P; Joly-Beauparlant, C; Droit, A; Trasler, J M; Kimmins, S; MacFarlane, A J; Benoit-Biancamano, M-O; Bailey, J L
Abstract: Persistent organic pollutants (POPs) can induce epigenetic changes in the paternal germline. Here, we report that folic acid (FA) supplementation mitigates sperm miRNA profiles transgenerationally following in utero paternal exposure to POPs in a rat model. Pregnant founder dams were exposed to an environmentally relevant POPs mixture (or corn oil) ± FA supplementation and subsequent F1–F4 male descendants were not exposed to POPs and were fed the FA control diet. Sperm miRNA profiles of intergenerational (F1, F2) and transgenerational (F3, F4) lineages were investigated using miRNA deep sequencing. Across the F1–F4 generations, sperm miRNA profiles were less perturbed with POPs+FA compared to sperm from descendants of dams treated with POPs alone. POPs exposure consistently led to alteration of three sperm miRNAs across two generations, and similarly one sperm miRNA due to POPs+FA; which was in common with one POPs intergenerationally altered sperm miRNA. The sperm miRNAs that were affected by POPs alone are known to target genes involved in mammary gland and embryonic organ development in F1, sex differentiation and reproductive system development in F2 and cognition and brain development in F3. When the POPs treatment was combined with FA supplementation, however, these same miRNA-targeted gene pathways were perturbed to a lesser extend and only in F1 sperm. These findings suggest that FA partially mitigates the effect of POPs on paternally derived miRNA in a intergenerational manner.